The impact of early marriage on women of reasonable age In The Special Region of Yogyakarta - Ratih Devi Alfiana; Linda Yulyani; Claudia Banowati Subarto; Sundari Mulyaningsih; Isti Chana Zuliyati (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2022)
Background: Early marriage is a form of violence and violation of children's rights. Early marriage that occurs in Indonesia is a very complex dynamic. Geographically, culturally and religiously, the level of acceptance and practice of child marriage varies across Indonesia. Based on the Report on the Fulfillment of Children's Rights in the Special Region of Yogyakarta in 2017, the number of child marriages in the Special Region of Yogyakarta was 294, a decrease from 2016 which was 346 (a decrease of 15.3%). Early marriage has a big risk of experiencing various bad things. Objective: to find out what are the impacts of early marriage on women of reproductive age in the Special Region of Yogyakarta. Methods: The data used in this study is secondary data from the Indonesian Health Demographic Survey (IDHS) issued by the BKKBN. The population in this study were all women of reproductive age whose data was recorded in the partner data in the 2017 IDHS report (Couples record). This research is an analytic study with a cross sectional approach. Data analysis was performed using Cremer's V and Contingency Coefficient analysis. Results: The results showed that there was an effect of early marriage on several dependent variables in this study which was indicated by p value <0.05. Some of these variables are education (p=0.002), Welfare Index (0.025), marital history (0.033). In addition, there is no significant relationship between the respondent's early marriage with employment, choice of contraceptive method, role in decision making, knowledge of reproductive health and knowledge of domestic violence.Conclusion: Reproductive health and sexuality education needs to be carried out strategically and systematically nationally and sustainably by involving various cross-sectors, starting from school education, community leaders, religious leaders and health workers. Appropriate and comprehensive teaching and education can help youth in making wise decisions regarding early marriage.